Evaluasi Kebergunaan dan Kredibilitas pada Aplikasi Pinjaman Kredit (Studi Kasus Home Credit) - Ayu Putu Augie Permata Dhea; Hanifah Muslimah Az-Zahra; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
This research has purpose to get evaluation result about usability and credibility aspects of the Home Credit Indonesia application by using usability and credibility questionnaire. The usability and credibility questionnaire by Zhao Huang is derived from English and translated into Bahasa Indonesia before be spread to the respondents. It has been validated from the linguist, ux expert, and ux academics. To get a valid usability and credibility questionnaire, this questionnaire has passed a pilot test after the expert validation. Then, the result will be counted through the validation and reliability test using product moment. Reference used to determine validity of each question is by using significance value. If the significance value is lower than 0,05 then the measurement is valid. But, if the significance value is more than 0,05 then the measurement is not valid. While, for the reliability test, it i referred to the Alpha Cronbach value. If Alpha Cronbach (Î±) value is more then 0,60 ( Î± > 0,60 ) then the data from research questionnaire is considered to be very good and consistent. After obtaining a valid and reliable questionnaire, then questionnaire distributed to the respondents. Therefore, 32 respondents were obtained which was fit to the criteria, that is the users who have used Home Credit application in credit lending. Based on the calculations and analysis of the respondents result, this research produced an evaluation in the form of an average value of usability and credibility aspect of Home Credit application. So that the results on the usability aspect are 12 out of 13 categories of assessment, showing results less than 3. Meanwhile, for aspects obtained 9 out of 13 categories, showing results less than 3.